The glycaemic index : a physiological classification of dietary carbohydrate - Wolever, Thomas M. S. (CAB books., 2006)
This book aims to provide a credible, complete and accurate source of information about all the aspects of glycaemic index. It contains chapters on glycaemic index definition and measurement and how glycaemic index information can be applied to meals and diets. Discussions on the reasons why foods have different glycaemic index values and the impact of altering the glycaemic index of diets on health and disease are presented as well.